Variations in directional wave parameters obtained from data measured using a GNSS buoy. (1st August 2020) - Lin, Yen-Pin; Huang, Ching-Jer; Chen, Sheng-Hsueh
Abstract: This study investigated variations in directional wave parameters by using various combinations of the GNSS buoy data, such as the displacements ( e n η ) and the velocities ( u v w ) in the east, north, and upward directions. The investigated directional wave parameters included mean wave direction, directional spreading, directional wave spectrum, and dominant wave direction (DWD). The three combinations of GNSS buoy data for determining the directional wave parameters were η u v, e n η, and u v w . Our results revealed that when the significant wave height ( H S ) values are ≥ 1 m, the signal-to-noise ratios (SNRs) for various measured items are sufficiently large, such that the directional wave parameters obtained from various data, such as e n η, u v w, and η u v, are identical. By contrast, under smooth to slight sea conditions with an H S of <1 m, the SNRs for the displacements are small. The small SNRs of e n η data tend to produce inaccurate directional wave parameters. The deviation in the mean wave direction and DWD obtained from the e n η data compared with those obtained from the u v w and η u v data decreases as the H S increases. For small seas, the u v w and η u v data are more appropriate than the e n η data for use in determining directional wave parameters. Highlights: Directional wave parameters were studied using different combinations of GNSS buoy displacement ( e n η ) and velocity ( u v w ) data. At high seas, the directional wave parameters determined from any of the three data sets were similar. At low seas, the u v w and η u v data are more appropriate for using to determine directional wave parameters.